(3GdYdGbGJ GdYGeI hGdYhdeI (B/s - (3GdMdjej, YHO GdQRGbs ((3YeGf(B: s (3OGQ LQjQ ddfTQ(B, s, 2004)
(3CgejI GdYdGbGJ GdYGeI, eQGMd fTCI GdYdGbGJ GdYGeI, GdGWGQ GdYGe dehGUaGJ GdYGedjf HGdYdGbGJ GdYGeI, eaGgje dgG YdGbI HGdYdGbGJ GdYGeI, GdUhQI GdPgfjI aj GdYdGbGJ GdYGeI, GdYdGbGJ GdYGeI hGdOHdheGSjI, GdYdGbGJ GdYGeI hGdYhdeI, GdYdGbGJ GdYGeI aj GdeLGd GdOhdj, OhQ GdYdGbGJ GdYGeI aj GdeDJeQGJ(B.s
(3GdeQGLY U(B.167s
Keywords: (3GdGJUGd GdLeGgjQjs; (3GdYdGbGJ GdYGeIs; (3GdYdGbGJ GdYGeI(B- (3GdYhdeIs